In-Hospital Outcomes of Acute ST Elevation Myocardial Infarction in Patients with Acute Kidney Injury (Cardiovascular Journal, 2018)
Background: Acute kidney injury (AKI) is a risk factor for long-term adverse outcomes, including acute myocardial infarction and death. The objective of this study was to find out in-hospital outcomes in patients with acute ST elevation myocardial infarction with acute kidney injury.Methods: A total 190 patients were included in this study and were equally divided into two groups, Group-I (with AKI) and Group-II (without AKI), according to absolute changes of serum creatinine level. AKI was defined as absolute changes in serum creatinine (SCr. at 48 hours’ minus admission SCr) and categorized as mild AKI (increase of 0.3 to